Exploring the Role of Microorganisms in Enhancing Pearl Millet Growth and Productivity: Microorganism role in pearl millet - Mohanram, Saritha; Naorem, Anandkumar; Kumar, Shrvan; Meena, Kamlesh Kumar; Panwar, Nav Raten (Annals of Arid Zone, 2023)
Arid and semi-arid regions are vast reservoirs of hardy organisms, including plant species and the associated microorganisms. An important crop of these regions is the pearl millet which serves as a source of food and feed, especially in the rainfed tracts. The inherent hardiness of the crop has attracted researchers from all over the world to unveil its underlying biology as well as to assess the role of associated microflora in imparting the hardiness that allow pearl millet to survive under very harsh climatic conditions. The pearl millet-associated microbiome consists of the rhizospheric (within the rhizosphere), phyllospheric (on the leaf surfaces) and endophytic (within the internal tissues) microbial communities. These microorganisms play a critical role in plant health and growth by improving the uptake of essential nutrients, protecting plants from pathogens, and enhancing drought and disease tolerance. This has been demonstrated in several studies wherein microbial inoculation of pearl millet resulted in increased protection from diseases like downy mildew, enhanced drought and high temperature tolerance and improved plant characteristics including yield. Exploring native stress tolerant and plant growth promoting microorganisms and unraveling their effect on molecular biology and biochemistry of pearl millet plants holds huge potential for their utilization in sustainable arid and semi-arid agriculture systems.